(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The telecom sector seeks to provide its services to customers in various categories, especially in mobile services, which contributed to the spread of a large number of these companies in the local environment, and mobile operators in this sector to diversify sources of revenue through a series of packages designed specifically to suit The various needs of customers throughout Iraq and the sustainability of their profits, and in view of the lack of requirements for recognition of revenue from the provision of such services in accordance with the unified accounting system applied in that sector, this study aimed to clarify the five steps to recognition of revenue according to me (The contract was concluded with a customer) at Cork Telecom Telecom to implement these requirements. The study reached a set of conclusions, the most important of which is the company’s recognition of the revenue and recording its value by the net amount (the amount received) On the date of the sale of the ( SIM Card) or the prepaid card to the agents or direct selling points and shall be considered as the final revenue of the Company excluding any discount given to the customer on the value of that commodity, contrary to the requirements of (IFRS 15), The company provide the committed service And the recognition of revenue for each service provided. Moreover, the amount of the discount is considered a reduction in the value of the recognized future revenues received from that customer. The adoption of the above standard gives an indication of the continuity of profits, which is a measure of the sustainability of profits. The value of the economic unit and make its departments work to sustain their accounting profits through the timing of recognition of revenue time to transfer the goods or service to the customer as well as determine the origin of the contract and the commitment of the contract depending on the performance of the economic unit in providing services to the customer, The study presented a number of recommendations, the most important of which is the development of the unified accounting system in accordance with the requirements of ( IFRS (15) and issuing instructions to companies to implement it.